Pengaruh Kecerdasan Emosional Terhadap Motivasi Belajar Peserta Didik Sekolah Dasar Gugus III Kecamatan Caringin - Nurlaeliah, Riska; Prasetyo, Teguh; Firmansyah, Wilis (Universitas Muhammadiyah Magelang, 2021)
This study aims to determine the significance of the effect of emotional intelligence on the learning motivation of elementary school students in cluster III Caringin District. The approach used in this study is a quantitative approach to the type of functional correlation with simple regression analysis, with a sample of 157 students. Data was collected using interview techniques and questionnaires with instruments in the form of interview guidelines and a psychological scale to measure each variable, namely emotional intelligence, and learning motivation. Based on the results of the t-test variables on motivation to learn emotional intelligence obtained t-count > t-table (5,065 > 1,960), then H0 is rejected and Ha is accepted, which means there is a partial effect of emotional intelligence to motivate learners Cluster III Elementary School in the District Caringin.